The new Black history : revisiting the second Reconstruction - Hinton, Elizabeth Kai, 1983-; Marable, Manning, 1950-2011 (Critical Black studies series., 2011)
The New Black History anthology presents cutting-edge scholarship on key issues that define African American politics, life, and culture, especially during the Civil Rights and Black Power eras. The volume includes articles by both established scholars and a rising generation of young scholars.